Oral Communication in Business and Industry: Results of a Survey on Scientific, Technical, and Managerial Presentations - Scheiber, H. J. and Hager, Peter J. (Journal of Technical Writing and Communication, 1994)
This research project focuses on the nature of oral presentations given (and produced) by scientific, technical, and managerial professionals working in business and industry. Our findings are survey-based; they reflect responses to a range of “issues” about technical/professional presentations, including these: 1) frequency; 2) target audience(s); 3) objectives; 4) types; 5) lengths; 6) data/information base; 7) use of visuals; 8) equipment; 9) obstacles; and 10) training. Our results indicate that presentations are frequently used in business, industry, and government and involve a wide variety of managerial audiences within organizations. Primary objectives of presenters surveyed are to inform (“sharing information”) and instruct/train.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC93NmxkLXVwaGYtazNidS1iMjNu